AGRICULTURE PROVIDES SUSTAINABILITY ISSUES OF AGRICULTURAL MARKET DEVELOPMENT - ALIEV; KASIMOV; RUZIEVA; NIGMATULLAEVA; ABDURAKHMANOV; DURMANOV (International Journal of Psychosocial Rehabilitation, 2020)
Events taking place on the global agricultural market show that the dynamics of growth in the production and export of agricultural products is observed in countries with natural and climatic advantages. International expert sin their studies on food security, they note the emergence of complex situations in the world and some of its regions related to this problem. The aim of the study is to develop scientifically based recommendations and suggestions for improving the scientific and practical basis for the proportional development of agricultural markets, agricultural resources and agricultural services in the conditions of modernization and intensive development of agriculture. The study used the methods of economic and statistical analysis in the study of the development of agricultural markets, agricultural resources and agricultural services, induction and deduction, accounting-constructive method, abstract thinking method, monographic observation methods. The practical results of the study the developed proposals for the proportional development of markets for agricultural products, agricultural resources and agricultural services can be used in the preparation of State programs for the development of agricultural markets. Most of the scientific results were used in practice in the system of the Ministry of Agriculture of the Republic of Uzbekistan. When making calculations, it is recommended that agricultural land, water resources, technical equipment, industrial buildings, productive and livestock, fixed production assets, environmental and climatic factors, oil products, mineral and organic fertilizers, working capital, credit and financial resources be included in the structure of agricultural resources.